Rehabilitation for the Paralytic Man? John 5 and an Aesthetics of Ambiguity - Dechant, James (Lumen et Vita, 2017)
The healing of the paralytic man in John 5 features what one commentator calls “one of the least defined characters in the Gospel.” When approached by Jesus and asked if he wants to be made well, the paralytic man responds indirectly about why he has not yet been healed (which could either arouse pity or come off as evasive); after his healing and second encounter with Jesus, he goes away and “tells the Jews that it was Jesus who had made him well” (which could be read as either brave witness or collaboration with an enemy). Most Johannine commentaries look unfavorably upon the man, though recent interpretations show more sympathy in light of the character’s low social status. In this paper, I argue that the man’s function in the story remains intentionally ambiguous in order to create a condition of uncertainty in the reader, one that leaves him/her with an undetermined experience of the text. This narrative technique allows readers to participate in the ambiguity experienced by the characters themselves. Our struggle to understand the man’s post- healing actions is not unlike his own struggle to comprehend his new state. Ambiguity then is not a textual obstacle to be overcome but a meaningful encounter with the text, to be welcomed. It ensures that our faith response is not predetermined. By renouncing certainty and embracing this “aesthetics of ambiguity,” we open ourselves to a potentially more transformative encounter with the Word. The inscrutability of the paralytic man should not frustrate us; it should affirm our own struggle to respond appropriately to radical new realities.